2007
DOI: 10.1111/j.1600-0463.2007.apm_548.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of home‐made resin salve from Norway spruce (Picea abies)

Abstract: Resin salve made from Norway spruce (Picea abies) is traditionally used in folk medicine to heal skin ulcers and infected wounds. Its antimicrobial properties were studied against certain human bacteria important in infected skin wounds. The sensitivity of the resin against Gram-positive and Gram-negative bacteria was studied in vitro by methods that are routinely used in microbiology laboratories. The resin salve exhibited a bacteriostatic effect against all tested Gram-positive bacteria but only against Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 21 publications
2
58
0
1
Order By: Relevance
“…The authors suggested that the mechanisms through which the resin inhibits the development of the microbes are "specific" (Rautio et al 2012). Similarly, extracts of P. abies show microbicidal activity against Gram-positive bacteria, but not against Gram-negative bacteria (Rautio et al 2007). Nevertheless, a different pattern was reported in the European Pharmacopoeia, with P. abies exerting a microbicidal activity against the Gram-negative bacteria, E. coli, and Pseudomonas aeruginosa (Sipponen and Laitinen 2011).…”
mentioning
confidence: 99%
“…The authors suggested that the mechanisms through which the resin inhibits the development of the microbes are "specific" (Rautio et al 2012). Similarly, extracts of P. abies show microbicidal activity against Gram-positive bacteria, but not against Gram-negative bacteria (Rautio et al 2007). Nevertheless, a different pattern was reported in the European Pharmacopoeia, with P. abies exerting a microbicidal activity against the Gram-negative bacteria, E. coli, and Pseudomonas aeruginosa (Sipponen and Laitinen 2011).…”
mentioning
confidence: 99%
“…Studies with bacteria suggest that this action causes nonspecific damage and is mediated by terpenic resin acids. [13][14][15][16] In electrophysiological experiments, exposure of S. aureus to resin decreases the cell membrane proton gradient in bacterial cells. This phenomenon is considered to be associated with a disruption in proton transport in the membrane-bound adenosine triphosphatase, resulting in the uncoupling of oxidative phosphorylation.…”
Section: Discussion Of Findings and Relevant Literature Mechanisms Ofmentioning
confidence: 99%
“…2,[8][9][10][11][12][13][14][15][16][17] As a result of this comprehensive translational research program, we have succeeded in showing through basic, clinical, and applied research that resin treatment in wound care is feasible and clinically effective. As far as we know, our research work regarding the medical use of spruce resin and its clinical applications in modern medicine are pioneering and globally unique.…”
Section: Translational Relevancementioning
confidence: 99%
See 2 more Smart Citations